Radioprotection applyed at assistencial routine in cardiac catheterization laboratories (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Our goal was evaluate if cardiologists and their team are compromising with radiation protection. This survey intends to support a study about  eyes lens opacity, also realized at SOLACI/2016-RJ-Brazil. An questionary about work conditions in cathlab, individual and colletive radioprotection, was applied for 127 professionals, being 95 cardiologists from several regions of Brazil, by means of personal interview. Among the responses, 38% said performed 50 procedures mensally while 43.7% between 50 and 100. Among them, 33.9% perform catheterims (CAT) and percutaneous coronary intervention (PCI), and 37% CAT, Ventriculography and  Coronary Artery Bypass Graft. Around 70% of professionals reported that they have been working for more than 10 years and most have answered that they routinely use protective tools such as lead apron and thyroid shield. Cardiologists answered that they did not routinely wear lead glasses (46%) and a suspended ceiling shield (33%). In general, they justified that the glasses do not fit perfectly on face. Around 27.6% answered that the radiologic equipment don’t have protective side shields. We verify that 39.4% have never received a formal training in radioprotection. We estimated that 63.8% wear dosimeters over the apron at chest level for personal doses control. The professionals reported that they work in public and private institutions and 28.6% reported working in more than two services. About 52.8% associate the use of lead aprons with acquired ergonomic diseases. We conclude that strategies should be established to reinforce  radiological protection practice and to guarantee better protection conditions for Cathlab professionals.